Intervenções para o tratamento da espasticidade muscular mastigatória em pacientes com paralisia cerebral. Revisão sistemática de ensaio clínico randomizado - Rocha, Monise Mendes (2020)
This review aimed to seek the effects of different interventions in the treatment of masticatory muscle spasticity in individuals with cerebral palsy. Randomized controlled trials (RCT) that evaluated the use of non-surgical interventions compared to the placebo group were considered, without intervention or any other active intervention. The interventions addressed were botulinum toxin, functional masticatory training and neuromuscular electrostimulation. Data such as decreased muscle spasticity, intensity of pain and adverse events, irritability and discomfort, as well as factors associated with muscle fatigue, breadth of mouth opening and prevention of tooth wear were analyzed. This review followed the recommendations of the Cochrane Manual for Systematic Reviews of Interventions and the PRISMA statement, and was recorded on the PROSPERO platform. A comprehensive literature search was performed using an electronic search (MEDLINE, Embase, Cochrane Library, LILACS, BBO, Clinicaltrials.gov and WHO / ICTRP) without restriction of date and language. Gray literature was also examined via OpenGrey. Two authors independently selected the references retrieved by the research strategy using the Rayyan software and extracted data from the included studies. All disagreements were resolved by a third author. The risk of bias assessment was performed using the RoB tool for RCTs. To estimate the effects of treatment, mean differences were calculated for continuous outcomes and risk rates for dichotomous outcomes (95% CI). The certainty of the set of evidence assessed by the GRADE approach was classified as very low due to methodological limitations and imprecision in the results.